2011
DOI: 10.1128/aem.00131-11
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Field Gel Electrophoresis Supports the Presence of Host-Adapted Salmonella enterica subsp. enterica Serovar Typhimurium Strains in the British Garden Bird Population

Abstract: Salmonellosis is a frequently diagnosed infectious disease of passerine birds in garden habitats within GreatBritain with potential implications for human and domestic animal health. Postmortem examinations were performed on 1,477 garden bird carcasses of circa 50 species from England and Wales, 1999 to 2007 inclusive. Salmonellosis was confirmed in 263 adult birds of 10 passerine species in this 11-year longitudinal study. A subset of 124 fully biotyped Salmonella enterica subsp. enterica serovar Typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…Investigations that describe the spatial, temporal, and molecular relationships of Salmonella outbreaks are paramount for piecing together how these outbreaks affect songbird populations. For example, a recent review of salmonellosis of garden birds in England showed that there are currently two host-adapted Salmonella phage types, S. Typhimurium DT40 and DT56v, that are circulating widely in British garden birds and that the reservoir of infection is maintained within wild bird populations (29). Based on these findings, it also appears that host-adapted Salmonella strains circulate among wild birds and are conserved for long periods of time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Investigations that describe the spatial, temporal, and molecular relationships of Salmonella outbreaks are paramount for piecing together how these outbreaks affect songbird populations. For example, a recent review of salmonellosis of garden birds in England showed that there are currently two host-adapted Salmonella phage types, S. Typhimurium DT40 and DT56v, that are circulating widely in British garden birds and that the reservoir of infection is maintained within wild bird populations (29). Based on these findings, it also appears that host-adapted Salmonella strains circulate among wild birds and are conserved for long periods of time.…”
Section: Discussionmentioning
confidence: 96%
“…Songbird S. Typhimurium isolates were distinctly different by MLVA from other avian isolates and belonged to one of two major clades, with finch isolates forming their own clade (IIIb). S. Typhimurium strains infecting passerines appear to be adapted to their avian host (24,29), but unlike other host-adapted S. enterica serovars (e.g., S. Gallinarum and S. Pullorum [7]), these avian strains appear to be capable of causing human illnesses (27).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella serovars Typhimurium and Enteritidis are two of the most common serovars reported among human Salmonella isolates worldwide (16). A study conducted in Great Britain on wild-bird populations was able to identify two host-adapted Salmonella serovar Typhimurium strains by use of pulsed-field gel electrophoresis (PFGE) and phage typing (PT) (17), demonstrating that host-associated subtypes can be identified even in broad-host-range serovars.…”
mentioning
confidence: 99%
“…Salmonella Typhimurium DT40 has not been detected in humans. Therefore, this DT40 strain was considered highly host-adapted to tree sparrows in Japan, thus maintaining a reservoir of infection as previously reported (Hughes et al 2008;Lawson et al 2011). This may rarely spill over to other species; however, deeper understanding of the epidemiology of sparrow salmonellosis is important for livestock and human health.…”
Section: Discussionmentioning
confidence: 91%
“…In Great Britain S. Typhimurium, with the definitive phage types (DT) 40 and DT56 variant, has been most frequently isolated from wild birds including House Sparrows (Passer domesticus) since the 1990s; it was hypothesized that these currently host-adapted strains are circulating and maintained within garden bird populations (Lawson et al 2011). Although these 'wild bird' strains have been isolated from various domesticated animals (Alley et al 2002;Rabsch et al 2002), they made up less than 0.5% of Salmonella isolates detected through livestock surveillance (Pennycott et al 2006).…”
Section: Introductionmentioning
confidence: 99%